HUBUNGAN AKTIVITAS FISIK TERHADAP KEBUGARAN KARDIORESPIRASI PADA ANAK USIA 9-12 TAHUN DI SD NEGERI 4 SIBANG GEDE - Gumilang, Kadek Gosha Arga; Ayu Vitalistyawati, Luh Putu; Made Reny Wahyu Sari, Ni Luh (Jurnal Fisioterapi dan Kesehatan Indonesia, 2023)
Physical fitness is very important for all people, especially children who are in the age range of 9-12 years who have quite busy activities such as playing. This research was conducted on May 29 and 31. The aim of this study was to provide an overview of the relationship between physical activity and cardiorespiratory fitness in children aged 9-12 years. This research is a quantitative study with a cross-sectional correlation method with one independent variable and one dependent variable. The sample in this study were 9-12 year old children at SD Negeri 4 Sibang Gede totaling 30 people who met the inclusion and exclusion criteria. Data collection in this study used the PAQ-C questionnaire and conducted cooper tests during the pre and post tests. Data were analyzed using the Pearson Product Moment Test. The results of this study showed a significance value in the deviation from linearity line of 0.491 which illustrates that the value of physical activity and cardiorespiratory fitness has a linear relationship. Based on the results of the Pearson product moment test, it was found that the value of P = <0.05 indicated that there was a correlation between the value of physical activity and cardiorespiratory fitness. The Pearson correlation value obtained is 0.790 which indicates a relatively strong level of correlation. It can be concluded that there is a relationship between physical activity and cardiorespiratory fitness in children aged 9-12 years at SD Negeri 4 Sibang Gede